Long-term efficacy and safety of pegvisomant in combination with long-acting somatostatin analogs in acromegaly - Neggers, S. J. C. M. M.; Franck, S. E.; De Rooij, F. W. M.; Dallenga, A. H. G.; Poublon, R. M. L.; Feelders, R. A.; Janssen, J. A. M. J. L.; Buchfelder, Michael; Hofland, L. J.; Jorgensen, J. O. L.; Van Der Lely, A. J. (Journal of Clinical Endocrinology and Metabolism, 2014)
Treatment for acromegaly patients with long-acting somatotropin release-inhibiting factor (LA-SRIF) often does not result in complete normalization of IGF-1. Addition of pegvisomant (PEGV), a GH receptor antagonist, could improve this; however, the literature has not described long-term follow-up.To assess long-term efficacy and safety of this combined treatment in the largest current single-center cohort of patients, from 2004-2013.Acromegaly patients were treated for at least 6 months with a high-dose LA-SRIF. To patients with persistently elevated IGF-1 levels (>1.2 × upper limit of normal) or poor quality of life, PEGV was added as one weekly injection.The patients (n = 141) were treated with PEGV and LA-SRIFs for a median period of 4.9 years (range, 0.5-9.2). Efficacy, defined as the lowest measured IGF-1 level during treatment, was 97.0%. The median PEGV dose to achieve this efficacy was 80 mg weekly (interquartile range, 60-120 mg). Combination treatment-related adverse events were recorded in 26 subjects (18.4%). Pituitary tumor size increase was observed in one patient. Injection-site reactions were observed in four subjects. In 19 patients (13.5%), transiently elevated liver transaminases of more than three times the upper limit of normal were observed, of which 83% occurred within the first year of combination treatment. Eight patients died, at a mean age of 71 years; none of them were considered treatment-related.The combination treatment with LA-SRIFs and PEGV was effective in 97% of the patients, it appears to be a safe medical treatment and it reduces the required dose of PEGV.
EVALuna2:22834